Overcoming Barriers for Foreign Language Speaking Skills - Astriani Aini; Aceng Rahmat; Nur Saadah Fitri Asih (Nusantara Science and Technology Proceedings, 2023)
Being able to communicate in a foreign language is one of the most important competencies in today's global era. However, there are still many students who have difficulty speaking even though they have studied for 3 years in high school or have even entered university level, their speaking ability is still not as expected. This research is in the form of a literature review, by examining any obstacles in speaking skills and how to overcome them. There are 4 barriers related to speaking skills, namely; school curriculum, speaking opportunities, classroom atmosphere, and talent myths. Cooperation and willingness of all parties are needed to improve students' speaking skills. Both policy makers, teachers, and students must work together to create a conducive learning environment. Like the school curriculum, there are still many who prioritize writing and listening skills, because the tests they face are mostly in the form of writing and listening tests. Understanding is needed for policy holders or teachers to explore a theme more than pursuing curriculum targets alone. The lack of opportunity to speak can be overcome by avoiding teaching by giving lectures. An unsupportive classroom atmosphere can lead to things that make learning motivation loss, lack of self-confidence, and the emergence of excessive anxiety. The assumption that good language is a talent is also something that is not entirely true. Effort and hard work remain an important point in obtaining success.